Control of wheeled mobile robot in restricted environment - Chang, Yong En (2017)
This project is a study of control of wheeled mobile robot in restricted environment. A wheeled mobile robot with 3 wheels is fabricated and it is control by a proportional derivative active force control (PD-AFC) to move in a pre-planned restricted environment to perform minimum track error. The kinematic and dynamic parameters of the mobile robot are considered. For the controller, a control system with two loops, outer and inner loop is designed to control the wheeled mobile robot. Fuzzy logic controller is implemented in the SIMULINK to estimate the Inertia Matrix that will be used to calculate actual torque applied on the wheeled mobile robot. The mobile robot is tested in circular path. The results are recorded and analyze. However, the movement of the wheeled mobile robot in actual path and desired path are compared.